Rocky Mountain Geo-Conference 2022 : proceedings of the Biennial Rocky Mountain Geo-Conference 2022, November 4, 2022, Westminster, Colorado - Arthurs, James M.; Strickland, Jere; Wiltshire, Richard L.; Malama, Joels C.; Wienecke, Christopher J. (Geotechnical practice publication ;, 2022)
Proceedings of the Rocky Mountain Geo-Conference 2022, held in Westminster, Colorado, November 4, 2022. Includes eight peer-reviewed papers on geotechnical practice and experience in Colorado and the Rocky Mountain west. Topics include: landslide repair, tunneling and tunneling rehabilitation, liquefaction studies for dams, diversity and equity, and wildfires and geotechnical assets.